Back-trajectory analysis of African dust outbreaks at a coastal city in southern Spain: Selection of starting heights and assessment of African and concurrent Mediterranean contributions. (September 2016) - Cabello, M.; Orza, J.A.G.; Dueñas, C.; Liger, E.; Gordo, E.; Cañete, S.
Abstract: The present study uses a back-trajectory analysis at multiple heights for better interpretation of the impact of the African dust outbreaks in the coastal Mediterranean city of Málaga (Spain), the southernmost large city in Europe. Throughout a 3-year period, 363 days were identified as dusty days by atmospheric transport models. During these events, PM10, SO2, O3, temperature, AOD and Ångström exponent showed statistically significant differences compared to days with no African dust. It was found that under African dust events, the study site was influenced by Mediterranean air masses at the lowermost heights and by Atlantic advections at high altitudes, while African air masses mostly reached Málaga at intermediate levels. Specifically, the lowest heights at which air masses reached the study site after having resided over Africa are confined into the 1000–2000 m range. The decoupling between the lowest heights and the ones for dust transport may explain the presence of aged air masses at the time of the African outbreak. Additionally, with the aim of studying the influence of the air mass origin and history on air quality, a new procedure based on Principal component analysis (PCA) is proposed to determine which altitudes are best suited as starting points for back-trajectory calculations, as they maximize the differences in residence time over different areas. Its application to Málaga identifies three altitudes (750, 2250 and 4500 m) and a subsequent analysis of back-trajectories for African dust days provided the main source areas over Africa as well as further insight on the Mediterranean contribution. Highlights: Study of African dust outbreaks in the southernmost largest European city. Proposed a new procedure to find the best starting heights for trajectory analysis. Decoupling in height may explain concurrent dust and aged pollutants load. At the lowermost levels flows are most frequently of Mediterranean origin. Lowest arrival height of African air masses mostly within 1000–2000 m.